Measuring Welfare Beyond GDP. (August 2019) - Aitken, Andrew
Abstract : Gross Domestic Product (GDP) is often treated as shorthand for national economic well-being, even though it was never intended to be; it is a measure of (some) of the marketable output of the economy. This paper reviews several developments in measuring welfare beyond GDP that were recently presented at the Economic Statistics Centre of Excellence (ESCoE) annual conference in May 2019. The papers discussed fall into three broad areas. First, a significant amount of work has focused on incorporating information about the distribution of income, consumption and wealth in the national accounts. Second, the effects of digitisation and the growth of the internet highlight the potential value in measuring time use as a measure of welfare. Third, the digital revolution has spawned many new, often 'free' goods, the welfare consequences of which are difficult to measure. Other areas, such as government services, are also difficult to measure. Measuring economic welfare properly matters because it affects the decisions made by government and society. GDP does a reasonable job of measuring the marketable output of the economy (which remains important for some policies), but it should be downgraded; more attention should be given to measures that reflect both objective and subjective measures of well-being, and measures that better reflect the heterogeneity of peoples' experiences.